Integrasi Manajemen Asset dan Liabilitas Perbankan Syari'ah - Parmujianto Parmujianto (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
Asset management focus and liability is to coordinate asset-liability portfolio of the bank in order to maximize profits for the banks and the results are distributed to the shareholders in the long term by taking into account liquidity needs and prudence. Prastimoyo (1997) says that the focus or objectives of management of assets and liabilities is to optimize revenue and keep the risk does not exceed the tolerable limit, while also maximizing the market price of the company's equity, while according to Bambang (2000), the management of assets and liabilities has a function and kenijakan in implementing a pricing strategy, both in the areas of lending and funding, in general, the responsibility of ALCO is to manage positions and allocation of funds that banks provided liquidity, maximize profit and minimize risk. On the other hand, Islamic banking has the characteristics berbada with conventional banks which do not recognize interest but for the results except that there are some business activities that exist only on Islamic banking such as trade and pawn so that it impacts extensive technical on banking activities one of which is the management asset-liabilit. So this paper will describe how the ALM policy applied to Islamic banking.